Development of interactive multimedia on learning geometry to improve understanding of elementary school children - Dedy Irawan; Ayyesha Dara Fayola; Rini Werdiningsih; Nurul Hikmah; Ridha Yuniara (Institute of Computer Science (IOCS), 2023)
The function of interactive multimedia in learning facilitates teachers' application of technology to the teaching and learning process and facilitates students' active and interactive learning with the aid of visualization media. Geometry is one of the hardest elementary school courses. There is a need for media that can represent complex material for easier comprehension, so that the research to build interactive multimedia on geometry learning can aid children in comprehending geometry material and boost student enthusiasm in learning geometry. The interactive multimedia development technique employs the ADDIE model because extremely useful for utilizing interactive multimedia to promote the growth of student comprehension and attainment of learning objectives. The results indicated that interactive multimedia learning geometry in elementary school can be an alternative learning medium can aid teachers in the teaching and learning process, particularly in simplifying the explanation of complex learning materials, and students can learn various forms of geometry visually and interactively, making it easier to comprehend and remember the material. Recommendations for additional study based on the questionnaire that can add to the sort of shape of the building space's geometry and can add personality and sound as a narrative of the provided material.